The Clash Between the Universal Declaration of Human Rights and Harmful Traditional Practices - Loisimaye, Naisiligaki; Tamthai, Mark (Bumi Publikasi Nusantara, 2024)
This paper has addressed the problem of harmful traditional practices in Tanzania and how such practices clash with the United Nations (UN) Universal Declaration of Human Rights (UDHR). This qualitative research has described the most persistent harmful traditional practices in Tanzania and suggested solutions to overcome the clash between UDHR and these practices. Findings reveal that child killings, son preference, and violence related to witchcraft accusations are the most persistent harmful traditional practices in Tanzania. To eliminate the harmful traditional practices problem in Tanzania, there is a need to enhance traditional justice systems within the framework of peace-building practice. For policy implication, there is a need to enhance effective policies that will act as problem-solving. Further, from time to time amendment of such established policies will help tackle emerging challenges on the problem. Lastly, a bottom-up approach should be adopted by engaging the locals in the whole process of formulating policies.